Artificial intelligence as a tool for increasing the efficiency of teaching foreign languages to medical students and their interest in this discipline - A. A. Shalavina; Yu. V. Shevtsova; S. V. Plotnova (Кардиоваскулярная терапия и профилактика)
Aim. To assess the significance and relevance of using artificial intelligence for teaching students interested in foreign languages.Material and methods. The study included a survey of students from the Privolzhsky Research Medical University, Lobachevsky State University of Nizhny Novgorod, and the Kstovsky Branch of the Arzamas Medical College, which took into account students' interest in using artificial intelligence in foreign language classes. A total of 256 students took part in the study.Results. The majority of surveyed medical students are interested in supplementing conventional foreign language classes with artificial intelligence programs, despite the presence of rare errors. Such a practice can improve academic performance.Conclusion. The conducted study confirmed the importance and relevance of using artificial intelligence in teaching foreign languages, especially regarding interested students. The analysis of open sources, as well as our own survey, showed that the integration of artificial intelligence into the educational process not only contributes to a deeper understanding of the language, but also makes learning more interactive and personalized. Students show a high interest in technologies that can adapt to their individual needs and learning style, which in turn increases motivation and the effectiveness of learning.